Functions and Values of Ritual “Larung Sesaji Kelud” in the local Community of Mount Kelud - Anam Miftakhul Huda; Atwar Bajari; Asep Saeful Muhtadi; Dadang Rahmat (MediaTor (Jurnal Komunikasi), 2017)
Larung sesaji kelud is a customary ritual that has a crater of Mount Kelud. It is a traditional Javanese cultural ceremony. This ceremony is held every month Suro (Javanese calendar). This ritual is held in the Sugihwaras Village, Ngancar District, Kediri. This research uses qualitative method. Qualitative method is a research procedure that produces descriptive data in the form of written or oral data of the people observed. The data in this research are the result of interview with informant and act of perpetrator of ceremony. Larung sesaji means to reject the oath of Lembu Suro vaunted by Goddess Kilisuci. “Yoh, Kediri mbesuk bakal pethuk piwalesku sing makaping-kaping, yaiku Kediri bakal dadi kali, Blitar dadi latar, lan Tulungagung dadi kedung " besides this sacred ritual as a form of gratitude to the god as a ruler, and also to reverence to the ruler of Mount Kelud. Larung sesaji Kelud as cultural preservation has spiritual values, as well as tourism asset so it can improve the economy of the surrounding community.